ANALISIS DETERMINAN PERTUMBUHAN EKONOMI DAN KEMISKINAN DI SUMATERA BARAT - Lili Manaulisda Fitri; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to explain the determinants of economic growth and poverty in West Sumatra. This study using Simultaneous Equation Model to determine the effect of exogenous variables on endogenous variable, the analysis uses Indirect Least Square (ILS) method. This study uses a data panel (cross section and time series) sourced from the Central Statistics Agency of West Sumatra. The analysis results show that labor, investment, and unemployment has a significant effect on economic growth, otherthat investment, unemployment, and education has a significant effect on poverty, and poverty has a significant effect on economic growth.